The value of Olympic success and the intangible effects of sport events: a contingent valuation approach in Germany - Wicker, P.; Hallmann, K.; Breuer, C.; Feiler, S. (European Sport Management Quarterly, 2012)
Olympic Games produce tangible and intangible effects that have been extensively researched; however, little is known on the importance of Olympic success to the population. The purpose of this study was to investigate the value of Olympic success using the contingent valuation method (CVM). The empirical evaluation is undertaken with data from a nationwide population survey in Germany (n 2006). Residents were asked to state their willingness-to-pay (WTP) for Germany being ranked first in the medal table and for a German winning a gold medal in track and field at the 2012 London Olympics. Average WTP amounts to t6.13 and t5.21, respectively. The regression results show that consumption capital and intangible factors were significant determinants of WTP. The findings can be integrated into cost-benefit analyses that are carried out for major sport events and can help justifying the use of taxpayer money to finance major sport events and elite sport development.